Protective coloration of animals - Thompson, John Augustus (My University, 1903)
Introduction: The protection of animals from their enemies by means of their coloration is one of the most interesting phases of evolution and also one of which we see many examples. The fact that such a protection exists has long been recognized, but until comparatively recently no systematic investigations have been made and no adequate explanation has been offered for its presence and the perfection to which this protection has been carried. Protective coloration is an advantage to animals for two purposes. 1st, they are rendered inconspicuous to that they may approach their prey. 2nd, they are concealed or protected from their enemies. The last object is effected in three ways. 1st, they are protected from their enemies by being made inconspicuous. 2nd, Inedible animas are protected by being made conspicuous. This method of coloration is called warning colors. 3d, Edible animals are protected by being made conspicuous to resemble inedible animals. This resemblance is called mimicry. These methods of coloration have been accounted for by three theories. 1st, Protective coloration has been imputed to a peculiarity originally created with the animals. 2nd, It has been claimed that it is caused by the direct action of the climate, surroundings, food, and habits of the animal. 3d, It has been accounted for by the theory of natural selection. The first theory does not admit of much discussion but it is very improbable, as the law of variations could certainly nave changed all the animals from their original type during the length of time they have existed.
Citation: Thompson, John Augustus. Protective coloration of animals. Senior thesis, Kansas State Agricultural College, 1903.
Morse Department of Special Collections
Keywords: Eduction of Women; Home Ties and Influence; Division of Income; Theses